If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = 10x + 15 Reorder the terms: 9 + 2x = 10x + 15 Reorder the terms: 9 + 2x = 15 + 10x Solving 9 + 2x = 15 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 9 + 2x + -10x = 15 + 10x + -10x Combine like terms: 2x + -10x = -8x 9 + -8x = 15 + 10x + -10x Combine like terms: 10x + -10x = 0 9 + -8x = 15 + 0 9 + -8x = 15 Add '-9' to each side of the equation. 9 + -9 + -8x = 15 + -9 Combine like terms: 9 + -9 = 0 0 + -8x = 15 + -9 -8x = 15 + -9 Combine like terms: 15 + -9 = 6 -8x = 6 Divide each side by '-8'. x = -0.75 Simplifying x = -0.75
| 2(2+-4)+t=16-t | | .25(16a-12)+15=33 | | p-3t=3 | | 4/5(x)+3=10 | | 0=-x^2+8x-9 | | 3x-4=x-7 | | 8y=5x+19 | | 9y=8(y+19) | | 12(z+12)=225 | | 3-4a-4a=a-16 | | v=3.14r(r)h | | x+2=-3x | | 7(x-3)-2(x-6)=9 | | -9+9a=-90 | | 8x+9-7x=15 | | 4x-2=-2x+10 | | 13x+2=11x-1 | | 4x-x=-9+7x | | 3(x-4)=2x-(x+3) | | -4-7=-2+x | | 10z=6z+16 | | 8x-29+9x=13+2x+2 | | 3(x-4)=2(x+5) | | 5x(2x-10)=40 | | 9z-z=2z-18 | | -4+9x+6=8x-2x | | 5(y-4)=10 | | 43=4(x+6)-1 | | 6x+2-9x=7x-5 | | -3x+8=5-2x | | 25+a=1-5(1-6a) | | 2(3x+7)=12-10 |